Tata Laksana Badai Tiroid di Instalasi Gawat Darurat - Sudadi; Pratomo, Bhirowo Yudo; Utomo, Wandito Gayuh (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
A thyroid storm is one of endocrinology emergency. Its incidence is very rare but has a very high mortality. Early diagnosis and aggressive treatment must be made in this case so that the patient has a good prognosis. Thyroid storm is often occurring in patients with hyperthyroidism who are not given adequate treatment and are triggered by infection, trauma, thyroid surgery, or uncontrolled diabetes mellitus. Initial treatment in Emergency Department includes assessment and management of the ABCDSs, appropriate intravenous (IV) fluid resuscitation, electrolyte replacement, precipitate factors management, and thyroid-specific therapy (include Anti Thyroid Drugs [ATDs], inorganic iodine, corticosteroid, betaAdrenergic Agonists [beta-AAs]). After getting proper treatment in Emergency Department, the patient must continue his care in the Intensive Care Unit (ICU) for clinical and treatment close monitoring. Therapeutic plasmapheresis (TPE) should be considered if clinical improvement is not noted within 24–48 hours of initial treatment.